Improving the surveillance of antimicrobial resistance trends amongst anaerobic oral pathogens. Issue 7 (30th September 2019) - Thomas, Dafydd; Scotford, Selina; Thomas, James; Crossland, James; Kelly, Grace; Morris, Trefor; Lewis, Michael; Wilson, Melanie
Abstract : Background: Orofacial infections when treated by dental practitioners are not routinely sampled for culture and susceptibility testing. Consequently, antimicrobial resistant rates amongst the causative bacteria are unknown, hindering efforts to appropriately manage these infections and undertake surveillance of resistant rates. As part of the Cardiff health board leadership in patient safety quality improvement programme a multidisciplinary group was tasked with the aim of improving sampling practices. Methods: Dental professionals' limited knowledge regarding the role of diagnostic support and an associated lack of confidence in sampling procedures was addressed by the creation and distribution of training aids. Sampling and transportation kits were developed and transport routes identified enabling dentists within the community setting to send samples to the specialist microbiology services based at Cardiff University Dental Hospital [UDH]. All significant anaerobes were identified and antibiotic susceptibility testing undertaken via agar dilution through referral of isolates to the UK Anaerobic Reference Unit. Results: A 10% increase was seen in the proportion of pus aspirates being received in comparison to pus swabs. For the first time, pus aspirate samples have been received from community dental clinics. A vast diversity of anaerob species and susceptibility profiles have been identified. Increasing rates of resistance amongst Prevotella species to amoxicillin and clindamycin is of concern. Conclusion: This project has shown that through educational interventions and support the barriers to the sampling of orofacial infections can be overcome. The ultimate aim is for all dentists in Wales to have access to diagnostic support.